Comparative Analysis Stock Price Volatility and Abnormal Return Before and After One Round Election (Event Study on the Composite Stock Price Index) - Ariani, Regita; Kristianto, Aloysius Hari (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This research aims to test and analyze the average of abnormal return and stock price volatility before and after the implementation of one round of elections. The method used in this research is event study (event study). The data period used in this research is 14 trading days, each of which is 7 days before and 7 days after the election. The focus of this research is on the IHSG on the Stock Exchange market. Data were analyzed using descriptive statistical techniques and statistical difference tests. Meanwhile, hypothesis testing uses test sone sample t test and test paried sample t test. Test results one sample t test shows there is abnormal return which is significant after the announcement of one round of election events, meanwhile the results of average test abnormal return those that have been tested have obtained significant differences abnormal return (AAR) before and after the event, however, the market responded positively to the one-round election event in Indonesia. while the results from the cumulative test are average abnormal return (CAAR), which researchers have tested, found that there was no significant difference in the cumulative average abnormal return (CAAR) before and after the one-round election event in Indonesia.